2013
DOI: 10.2169/internalmedicine.52.8760
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Cerebral Air Embolism Developing within the Posterior Circulation Territory after a Needle Lung Biopsy

Abstract: We herein report the case of a 75-year-old woman with a paradoxical cerebral air embolism (CAE). She developed a bilateral visual disturbance at the time of needle puncture during a computed tomography (CT)-guided percutaneous needle lung biopsy in the face down position. The air density within the descending aorta on chest CT suggested the presence of a cerebral air embolism. Brain MRI demonstrated increased signal intensity in the bilateral occipital lobes on diffusion-weighted images. Usually, CAE occurs pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Others [ 2 , 9 ] detected intracranial air on CT scans performed less than 7 hours after the onset of CAE. While Jeon et al [ 2 ] reported that brain CT performed 38 hours after the onset of CAE still showed multiple punctate air densities in the left frontal subcortices, Suzuki et al [ 3 ] detected no air density on brain CT scans acquired 30 minutes after the onset of CAE considered as arterial. When dogs were injected with 0.5 or 2 mL of air directly into the carotid artery, 50% and 100% of the animals, respectively, manifested arterial CAE; the half-life of air absorption was approximately 8 minutes [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others [ 2 , 9 ] detected intracranial air on CT scans performed less than 7 hours after the onset of CAE. While Jeon et al [ 2 ] reported that brain CT performed 38 hours after the onset of CAE still showed multiple punctate air densities in the left frontal subcortices, Suzuki et al [ 3 ] detected no air density on brain CT scans acquired 30 minutes after the onset of CAE considered as arterial. When dogs were injected with 0.5 or 2 mL of air directly into the carotid artery, 50% and 100% of the animals, respectively, manifested arterial CAE; the half-life of air absorption was approximately 8 minutes [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral air embolism (CAE) is a well-known complication of trauma, central venous catheterization, pressurized intravenous infusion systems, and orthopedic, neurosurgical, and cardiovascular surgical procedures [ 1 ]. Some CAEs can be identified on brain computed tomography (CT) scans and subsequent infarcts on diffusion-weighted images (DWI) [ 2 , 3 ]. However, changes in the distribution and amount of intracranial air have not been demonstrated in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 presents this study’s PRISMA flow diagram, which summarizes the screening process and the reasons for exclusion. A total of 104 studies 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , …”
Section: Resultsmentioning
confidence: 99%
“…In humans diagnosed with decompression sickness, CT and MRI imaging is often unable to identify gas emboli (55,56), and in a consecutive series of 16 patients referred for hyperbaric treatment at one institution after presumed SAGE who underwent imaging, only 2 demonstrated abnormalities on CT or MRI despite ongoing symptoms (57). One report of cerebral gas embolism after percutaneous lung biopsy was unable to demonstrate intraparenchymal gas even on CT 30 minutes after the clinical event (58), and another showed complete resolution of previous "massive" gas emboli only two hours after the event (27). Brain MRI often reveals widespread areas of restricted diffusion which do not correlate with affected areas visualized on CT (59); these infarcts may be related to the after-effects of vasospasm and vascular inflammation, which remain despite rapid gas resorption.…”
Section: Diagnostic Imagingmentioning
confidence: 99%